High-mobility pentacene thin-film phototransistor with poly-4-vinylphenol gate dielectric - Kwon, Jae-Hong; Chung, Myung-Ho; Oh, Tae-Yeon; Bae, Hyeon-Seok; Park, Jung-Ho; Ju, Byeong-Kwon; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2009)
An organic thin-film transistor was fabricated with pentacene as the active material and poly(4-vinyl phenol) as the gate-dielectric material. Atomic force microscope image shows that the pentacene film grows in the polycrystalline structure of the poly-4-vinylphenol (PVP) dielectric layer with the surface root-mean square (RMS) roughness of 6.0 nm and average grain size of 800 nm. The pentacene thin-film transistor exhibited a saturation field-effect mobility of 1.64 cm(2)/V s, a threshold voltage of -18 V, a sub-threshold swing of 3.53 V/decade, on/off-current ratio of 7.1 x 10(4) and interface trap density of 5.39 x 10(12) eV(-1) cm(-2). The higher mobility of pentacene on poly(4-vinyl phenol) layer is attributed to the larger grain size of the pentacene. The photoresponsive properties of the organic thin-film transistor were investigated under various illumination intensities. The photosensitivity was measured as 1.46 at an illumination intensity of 100 mW/cm(2) at the off state. This suggests that the pentacene thin-film transistor shows a phototransistor behavior. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Organic thin-film transistor; Pentacene; Poly-4-vinylphenol; Photoresponse